The recent rise of Christian Zionism in Brazil: church life and politics - Freston, Paul (Religion, state & society, 2025)
This contribution analyses the recent rise of a highly politicised form of Christian Zionism in Brazil, situating it within the broader expansion of evangelical and Pentecostal political engagement. While Christian Zionism has been extensively studied in the United States, its manifestations in the Global South remain understudied. The contribution challenges US-centric interpretations by tracing the historical development of Christian Zionist discourse in Brazil and examining how it became a significant force in parliamentary and foreign policy debates, particularly during the Bolsonaro administration (2019–2022). Drawing on documentary analysis of Brazilian congressional records, government websites, and religious organisations, as well as interviews with key actors, the study demonstrates that Brazilian Christian Zionism combines theological, political, and geopolitical dimensions. It identifies distinct forms of Christian Zionism – prophetic, prosperity-driven, covenantal, and cultural – as prominent in shaping Brazil’s parliamentary and diplomatic alignment with Israel. This work contributes to the literature on religion and politics by highlighting the role of transnational religious networks in reshaping Brazil’s foreign policy and evangelical identity. Ultimately, it argues that Christian Zionism in Brazil is a complex and dynamic phenomenon that reflects both global trends and specific local political and religious contexts.